Gaborone call to action on noncommunicable diseases to achieve Sustainable Development Goals #3 - Davison Munodawafa (Medknow Publications, 2023)
We express deep appreciation, as technical resource persons and experts from the Africa region convened here under the World Noncommunicable Diseases (NCDs) Federation and the World Health Organization (WHO) in Gaborone, Botswana, from December 12 to 14, 2018 to examine challenges and best actions We acknowledge that Framing the NCDs Response and addressing of Sustainable Development Goals (SGDs) in the African Region require leadership and technical expertise to deliberate and reach consensus on key strategies and policies